Estresse oxidativo e metabolismo ósseo em modelo roedor de síndrome dos ovários policísticos (SOP) - Mujica, Lady Katerine Serrano (2020)
Polycystic ovary syndrome (PCOS) is considered the commonest cause of endocrine infertility in women and affects around 8% of females at reproductive age. It is a complex disturbance, frequently associated with insulin resistance, increase of inflammatory markers, oxidative stress, dyslipidemia, and an increased risk to the development of cardiovascular disease and diabetes. Recently, it has been considered the possibility that PCOS may affect the bone metabolism directly or indirectly. In rats, neonatal androgen or estrogen excess replicate similar metabolic and reproductive abnormalities seen in human PCOS. Indeed, studies with animal models have been carried out to confirm the origins of PCOS. Among the models employed are those based on the administration of testosterone propionate. Therefore, the present work has the main aim to study a rodent animal model of PCOS induced by testosterone propionate and evaluating metabolic, oxidative stress, and its impact on the bone tissue. Study findings indicate that changes in oxidative stress could be promoted by testosterone propionate exposure after birth, which is likely associated with anovulation and/or lipid disarrangement.